Interfaith Marriage and the Religion–State Relationship: Debates between Human Rights Basis and Religious Precepts - Maula, Bani Syarif; Muhsin, Ilyya (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Following the Constitutional Court’s dismissal of the judicial review of Article 2, Paragraph 1 of the Marriage Law, the Jakarta Central District Court granted approval for the registration of inter-religious marriages. The issue of inter-religious marriage has once again become a hot topic of social discussion. Following the controversy, the Supreme Court issued a circular ordering the court not to grant marriage registration applications for interfaith couples. This study draws on normative legal research and empirical analysis of interfaith marriages to answer the question of how states (through courts) view and negotiate interfaith marriages from state, legal, and religious perspectives. The objective of this study is to examine the arguments presented by proponents and opponents of interfaith marriage in Indonesia, particularly focusing on the discourse surrounding human rights principles and the adherence to religious teachings within the realm of marital practices. The study concluded that Islamic law remains one of the most fundamental elements of contemporary Muslim family life practices in Indonesia. All religions, including government officials and judges, generally consider interfaith marriages illegal and prohibit them under the Marriage Act. The Constitutional Court's decision to deny judicial review of the provisions governing interfaith marriage reinforces the argument that, in terms of the relationship between religion and the state, Indonesia falls into the category of countries with religiously governed enclaves.